2008
DOI: 10.1212/01.wnl.0000304121.57857.38
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab for recurrent malignant gliomas

Abstract: Combination therapy with bevacizumab and chemotherapy is well-tolerated and active against recurrent malignant gliomas. At recurrence, continuing bevacizumab and changing the chemotherapy agent provided long-term disease control only in a small subset of patients. Bevacizumab may alter the recurrence pattern of malignant gliomas by suppressing enhancing tumor recurrence more effectively than it suppresses nonenhancing, infiltrative tumor growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

37
601
2
19

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 761 publications
(659 citation statements)
references
References 28 publications
37
601
2
19
Order By: Relevance
“…This allows the differential hypothesis of antiangiogenic therapy failing at the tumor-vascular interface, probably because of altered physiological, metabolic conditions in close proximity to the vessel. Norden et al [20] looked at 55 BEV-treated and 19 control patients. Although they did not demonstrate a difference in recurrence patterns between both groups, they concluded that there might occur a relevant discordance between the T1+c and the FLAIR appearance of the recurrent BEV-treated tumors.…”
Section: Evidence Of Increased Frequency Of Remote Relapse With Bev Tmentioning
confidence: 99%
See 2 more Smart Citations
“…This allows the differential hypothesis of antiangiogenic therapy failing at the tumor-vascular interface, probably because of altered physiological, metabolic conditions in close proximity to the vessel. Norden et al [20] looked at 55 BEV-treated and 19 control patients. Although they did not demonstrate a difference in recurrence patterns between both groups, they concluded that there might occur a relevant discordance between the T1+c and the FLAIR appearance of the recurrent BEV-treated tumors.…”
Section: Evidence Of Increased Frequency Of Remote Relapse With Bev Tmentioning
confidence: 99%
“…It may happen that despite persistent reduction in contrast enhancement an increase in non-enhancing T2 or FLAIR signal alterations suggestive of infiltrative tumor develops [11,19,20]. This dissociation is called "discordance" between the information gathered on T1+c and T2 images [20,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although angiogenesis inhibitors targeting the vascular endothelial growth factor (VEGF) signalling pathway are efficacious, a growing body of evidence suggests that, after an initial response with vascular dropout and tumour stasis, pharmacologically impaired angiogenesis can eventually act as a detrimental driving force for enhanced tumour cell invasion into surrounding tissue, a process commonly referred to as 'evasive resistance' (Casanovas et al, 2005;Paez-Ribes et al, 2009). In clinical series, upon progression on antiangiogenic therapy with the VEGF-directed antibody bevacizumab, glioblastomas may display a more infiltrative pattern of recurrence (Norden et al, 2008b). To overcome this often insidious consequence and optimize antiangiogenic therapies, it is a major challenge integrating antiangiogenic with antiinvasive mechanisms into one combined treatment concept.…”
Section: Introductionmentioning
confidence: 99%
“…27,28,32,[38][39][40][41][42][43][44][45][46][47] In addition, several retrospective studies have also been reported combining bevacizumab and irinotecan; carboplatin; carboplatin and cetuximab; carboplatin, etoposide, and ifosfamide; lomustine; carmustine; etoposide; or temozolomide. [48][49][50][51][52][53][54][55][56][57][58] Although these small studies are not easily compared due to their size and various patient populations, the consensus to date has been that no combination significantly surpasses the outcomes of bevacizumab monotherapy for recurrent glioma. 9 …”
Section: Early Study Of Bevacizumab In Patients With Recurrent Glioblmentioning
confidence: 99%